PENGARUH KOMUNIKASI DAN PELATIHAN TERHADAP KUALITAS PELAYANAN KARYAWAN KEBUN RAYA PURWODADI PASURUAN - Arum Widiatul Aini; Adriani Kala’lembang (LPPM Universitas Nias Raya, 2024)
This study aims to determine the impact of Communication and Training on the Service Quality of employees at Kebun Raya Purwodadi Pasuruan. The research was conducted quantitatively with a population of 77 employees. Before the data collection, the questionnaire was tested for validity and reliability. Data analysis was performed using multiple regression analysis. The findings show that (1) Communication has an effect on Service Quality, indicated by a regression coefficient of 0.309 and Tvalue (4.056) > Ttable (1.992), with a significance level of 0.000 < 0.05. (2) Training also has an impact on Service Quality, with a regression coefficient of 0.217 and Tvalue (2.311) > Ttable (1.992), and a significance level of 0.024 < 0.05.